Collective Visioning: Igniting the Radical Imagination - York, Matt (Radical Teacher, 2020)
As the spaces which once existed within the university for the co-imagining of liberatory political praxes diminish, social movements are increasingly reverting to methods of collective visioning which have been developed on the streets to theorise radical social change. I argue that such methodologies provide important opportunities for a reappraisal of our hierarchical student/teacher relations, and make the case that we can collectively learn much more from within our movements than anyone might hope to teach us from outside. The article traces our current movement wave, and locates contemporary forms of collective visioning within a wider lineage of knowledge co-production in social movements. The neoliberal subversion of university education is examined, and proposals made for ways in which we might challenge these hegemonic conditions. I conclude that the liberatory epistemologies and forms of knowledge co-production explored in this article offer significant potential for developing new modes of praxis for our current wave of ecological and anti-capitalist activists both inside and outside the university.